2022
DOI: 10.3390/v14122812
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity as Risk Factors for Recurrent Herpetic Stromal Keratitis during Long-Term Antiviral Prophylaxis

Abstract: Although past research has shown an association between obesity and herpes simplex virus infection, the relationship between body mass index (BMI) and herpetic stromal keratitis (HSK) recurrence has never been investigated. In this study, we included HSK patients who received oral valacyclovir as prophylactic treatment between January 2016 and January 2021. Recurrence, possible risk factors, and the time to recurrence were recorded during follow-ups. Among the 56 patients included in this study, recurrence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies have shown that obese and overweight individuals are more likely to develop recurrent simplex keratitis[ 158 ]. The use of corneal impression membranes led to higher detection of HSK compared to swab techniques[ 159 ].…”
Section: Diagnostic Approaches For Herpes Simplex Keratitis: Challeng...mentioning
confidence: 99%
“…Studies have shown that obese and overweight individuals are more likely to develop recurrent simplex keratitis[ 158 ]. The use of corneal impression membranes led to higher detection of HSK compared to swab techniques[ 159 ].…”
Section: Diagnostic Approaches For Herpes Simplex Keratitis: Challeng...mentioning
confidence: 99%